The Factor Determining Effective Modelling of the Urban Spatial Transformation Process Based on Temporary Use - SZATON-ORLIŃSKA Karolina; OPANIA Szymon (Architecture, Civil Engineering, Environment)
The research involves analysing strategic models of urban spatial transformation processes in cities using temporary use as a significantly supportive tool or as the core of the transformations. The scope of the research includes identifying effective transformation models through the verification of cases based on established criteria and conducting detailed studies of selected cases to highlight the process elements, analyse their relationships, and assess the role of temporary use. The research method relies on critically comparing and analysing chosen cases. As a result, we have identified fundamental criteria that indicate the application of temporary use as part of a broader transformation process, along with supplementary indicators and characteristics that impact the effectiveness of the conducted transformations. These indicators can help model transformation processes based on temporary use. The research holds particular significance in utilizing temporary use within a broader, integrated urban transformation process that goes beyond a one-time intervention.